Erste Allgemeine - Generali Foundation : Sammlung Österreichische Skulptur. - Breitwieser, Sabine; Drechsler, Wolfgang; Karner, Dietrich; Köb, Edelbert; Reder, Christian; Sotriffer, Kristian; Zweite, Armin (Wien : Erste Allgemeine - Generali Foundation, 1990)
X, Robert Adrian ; Auer, Sepp ; Avramidis, Joannis ; Dabernig, Josef ; Egerer, Evelyne ; Erjautz, Manfred ; Feiersinger, Werner ; Gironcoli, Bruno ; Goeschl, Roland ; Graf, Franz ; Kaligofsky, Ad ; Kölbl, walter ; Kopf, Willi ; Kowanz, Brigitte ; Kupelwieser, Hans ; Lutz, Christian ; Maderna, Marianne ; Moser-Wagner, Gertrude ; Moswitzer, Gerhard ; Obersteiner, Gerald ; Ölzant, Franz Xaver ; Painitz, Hermann J. ; Pichler, Franz ; Pinter, Klaus ; Prantauer, Christine Susanna ; Schellander, Meina ; Stimm, Oswald ; Stimm, Thomas ; Strobl, Ingeborg ; Tandon, Rini ; Traar, Jochen ; Trattner, Josef ; Wakolbinger, Manfred ; Walde, Martin ; Weibel, Peter ; Weigand, Hans ; Weinberger, Lois ; West, Franz ; Wurm, Erwin ; Zobernig, Heimo
Duits
kunstcatalogus
Keywords: Oostenrijk